Programming Puzzles: Python Edition. - Matthew Whiteside; PACKT (GB: Packt, 2024)
"Programming Puzzles" by Matthew Whiteside offers an engaging collection of challenge and fun puzzles designed to sharpen your problem-solving skills and enhance your programming expertise Key Features A diverse range of puzzles to suit different skill levels Hints and solutions to facilitate learning and understanding Comprehensive explanations that deepen programming knowledge Book Description "Programming Puzzles" is a meticulously crafted collection designed to elevate your coding skills through engaging and challenging exercises. The book begins with a helpful guide on getting started, ensuring that readers are well-prepared to tackle the puzzles ahead. As you delve deeper, you'll encounter a series of challenge puzzles that test your logical thinking and problem-solving abilities, followed by fun puzzles that offer a more relaxed yet equally rewarding experience. Hints are provided for the challenge puzzles to guide you through particularly tough spots, ensuring you stay motivated without giving away the solutions. Once you've worked through the puzzles, comprehensive solutions are provided, allowing you to understand different approaches and learn from your mistakes. Each section of the book is designed to progressively build your skills, from basic logic to advanced problem-solving techniques, making it an invaluable resource for anyone looking to improve their programming abilities. The journey through this book is not just about finding solutions; it's about developing a deeper understanding of how to approach and solve complex problems. By the end of this book, you'll have honed your coding skills, enhanced your logical thinking, and gained a new appreciation for the art of problem-solving in programming. What you will learn Develop logical thinking and problem-solving skills Apply programming concepts to solve challenging puzzles Enhance coding proficiency through practical exercises Gain insight into different approaches to problem-solving Understand the logic behind complex programming solutions Improve debugging skills with detailed solution explanations Who this book is for The ideal audience for "Programming Puzzles" includes software developers, data scientists, computer science students, coding bootcamp graduates, and anyone preparing for technical interviews. This book is perfect for individuals looking to enhance their problem-solving and coding skills through a variety of engaging and challenging puzzles. A basic understanding of programming concepts and familiarity with the programming language are recommended prerequisites to fully benefit from the exercises and solutions provided.
Data in extended ASCII character set.
Mode of access: Internet.